Flexible shielding composite material and preparation method thereof

By hot melt blending of polyurethane, polypyrrole and modified carbon black, a flexible shielding composite material was prepared, which solved the problem of insufficient shielding performance of existing materials in flexible electronic devices and achieved efficient electromagnetic shielding and good flexibility and flame retardant properties.

CN119410130APending Publication Date: 2025-02-11ANHUI RUIXILDE NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411766970.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing electromagnetic shielding materials are difficult to meet the high deformation requirements in flexible electronic devices, and their shielding performance is insufficient, so they cannot effectively suppress electromagnetic radiation.

Method used

Polyurethane and polypyrrole are used as substrates, combined with modified carbon black and lubricant, and hot melt blending is carried out through a twin-screw extruder to prepare a flexible shielding composite material. The modified carbon black improves compatibility and dispersion with the polyurethane matrix through surface modification, thereby enhancing the electromagnetic shielding performance of the material.

Benefits of technology

The obtained flexible shielding composite material has excellent electromagnetic shielding, flexibility and flame retardancy, which can effectively suppress electromagnetic radiation and maintain stable performance during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169210590000031
    Figure BDA0005169210590000031
  • Figure BDA0005169210590000032
    Figure BDA0005169210590000032
  • Figure BDA0005169210590000041
    Figure BDA0005169210590000041
Patent Text Reader

Abstract

The invention discloses a flexible shielding composite material and a preparation method thereof, and belongs to the technical field of electromagnetic shielding. Comprising the following raw materials in parts by weight: 60-80 parts of polyurethane, 25-35 parts of polypyrrole, 12-28 parts of modified carbon black and 4-6 parts of a lubricant. Polyurethane is used as a matrix, so that the material is endowed with excellent flexibility; wherein the polypyrrole enhances the electromagnetic shielding property of the composite material; wherein compared with common carbon black, the modified carbon black has better compatibility with a polyurethane matrix, the agglomeration phenomenon is obviously reduced, the modified carbon black is more easily dispersed in the matrix, the flame retardance, shielding property and flexibility of the composite material are greatly enhanced, and the modified carbon black has long and stable performance and is not easy to fall off; therefore, the prepared composite material has stable and efficient electromagnetic shielding property, flexibility and flame retardance, and has important application value in the technical field of electromagnetic shielding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electromagnetic shielding, and in particular, relates to a flexible shielding composite material and a preparation method thereof. Background Art

[0002] Shielding materials refer to functional materials that can attenuate the propagation of electromagnetic wave energy by absorption, reflection, etc., so as to effectively suppress electromagnetic interference and pollution. This type of material is mainly used to curb the influence of high-frequency electromagnetic fields. By forming eddy currents in the shielding body and reflecting at the interface between the shielding body and the protected space, the field strength of the interference field in the protected space is greatly weakened. They have important applications in materials science, especially in modern society where electronic devices are increasing. Shielding materials are essential to protect equipment performance and human health.

[0003] In recent years, flexible electronic technology has received great attention. However, like traditional electronic devices, flexible electronic devices will also generate electromagnetic radiation pollution during operation. Therefore, shielding materials are needed to shield electromagnetic radiation. However, current electromagnetic shielding materials are almost all developed for traditional rigid electronic devices, with poor flexibility, and it is difficult to meet the high deformation requirements of flexible electronic devices for shielding materials. Common flexible materials include polyethylene, polypropylene, polyester, polyamide, polydimethylsiloxane, polyurethane, etc., but these materials themselves have poor shielding properties and cannot meet the needs of electromagnetic shielding materials. Therefore, it is urgent to invent a composite material that is both flexible and electromagnetic shielding to meet the higher demands in the field of electromagnetic shielding technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a flexible shielding composite material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a flexible shielding composite material comprises the following steps:

[0007] The polyurethane and polypyrrole are dried, added into a mixer with modified carbon black and lubricant, stirred evenly, and then put into a twin-screw extruder, set the temperature to 200-220° C., melt blend for 30-60 minutes, and extrude to obtain a flexible shielding composite material.

[0008] Furthermore, the raw materials are calculated in parts by weight as follows: 60-80 parts of polyurethane, 25-35 parts of polypyrrole, 12-28 parts of modified carbon black, and 4-6 parts of lubricant.

[0009] Furthermore, the lubricant is one of stearic acid and paraffin.

[0010] With polyurethane as the matrix, polyurethane has excellent flexibility and can maintain its shape and elasticity during continuous deformation, giving the material excellent flexibility; the introduction of polypyrrole, a common conductive polymer, enhances the electromagnetic shielding properties of the material.

[0011] Furthermore, the modified carbon black is prepared by the following steps:

[0012] S1. In a three-necked flask equipped with a stirring reflux device, 2,2,6,6-tetramethylpiperidinol, n-octane and molybdenum trioxide were mixed and stirred uniformly, and tert-butyl hydroperoxide aqueous solution was added dropwise, and stirring was performed while dropping until the addition was completed. The reaction temperature was controlled to 75°C, and the reflux reaction was carried out for 6 hours. After the reaction was completed, the filtrate was filtered, and activated carbon was added to the filtrate and stirred for 1 hour. The mixture was allowed to stand, filtered, and the filtrate was taken. The n-octane was removed by distillation under reduced pressure to obtain intermediate 1; the ratio of the amount of 2,2,6,6-tetramethylpiperidinol, n-octane, molybdenum trioxide and tert-butyl hydroperoxide aqueous solution was 15.7 g:75 mL:0.2 g:15 mL;

[0013] Under the catalysis of molybdenum trioxide and the oxidation of tert-butyl hydroperoxide, 2,2,6,6-tetramethylpiperidinol and n-octane undergo a free radical coupling reaction; n-octane participates in the reaction process as a reactant and also acts as a reaction solvent, which can reduce the formation of by-products to obtain intermediate 1; the specific reaction process is as follows:

[0014]

[0015] S2. In a three-necked flask equipped with a stirring device, terephthalic acid, intermediate 1 and N,N-dimethylformamide (DMF) were stirred and mixed uniformly, 4-dimethylaminopyridine (catalyst) and dicyclohexylcarbodiimide (DCC, dehydrating agent) were added, the reaction temperature was controlled to 75°C, and the reaction was kept warm for 8 hours. Stirring was continued during the reaction. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by vacuum distillation. The mixture was then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate in a volume ratio of 4:1), and the eluent was removed by rotary evaporation to obtain intermediate 2; the ratio of the amount of terephthalic acid, intermediate 1, N,N-dimethylformamide, 4-dimethylaminopyridine and DCC was 18.1 g: 28.5 g: 150 mL: 0.2 g: 20.6 g;

[0016] Under the catalysis of dibutyltin oxide and DCC, the carboxyl group on terephthalic acid and the hydroxyl group on intermediate 1 undergo esterification reaction. By controlling the molar ratio of the two to be close to 1:1 and the terephthalic acid to be slightly excessive, only one carboxyl group on terephthalic acid participates in the reaction to obtain intermediate 2. The specific reaction process is as follows:

[0017]

[0018] S3. Add 4,4'-diaminodiphenyl sulfone and N,N-dimethylformamide (DMF) to a three-necked flask equipped with a stirring device, mix, heat to 30°C and stir continuously until the solid is completely dissolved, introduce nitrogen to exclude air, add intermediate 2 and DCC, mix and stir evenly, place in a 55°C water bath, stir and react for 4 hours, filter after the reaction, remove the solvent by vacuum distillation, wash with anhydrous ethanol 2-3 times, and vacuum dry to obtain intermediate 3; the ratio of 4,4'-diaminodiphenyl sulfone, N,N-dimethylformamide, intermediate 2, and DCC is 25.7g:150mL:43.3g:20.6g;

[0019] The amino group on 4,4'-diaminodiphenyl sulfone and the carboxyl group of intermediate 2 undergo an amidation reaction. Under the action of DCC, the reaction can be carried out under relatively mild conditions. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of 4,4'-diaminodiphenyl sulfone, only one amino group on 4,4'-diaminodiphenyl sulfone participates in the reaction to obtain intermediate 3. The specific reaction process is shown below:

[0020]

[0021] S4, mixing oxidized carbon black with N,N-dimethylformamide, ultrasonically treating for 15 minutes to make the oxidized carbon black evenly dispersed, adding intermediate 3 and DCC, magnetically stirring for 2 hours, placing in a 55°C water bath for 4 hours, removing the water bath and magnetically stirring at room temperature for 6 hours, filtering, washing with anhydrous ethanol 3-4 times, drying, grinding, and obtaining modified carbon black; the ratio of oxidized carbon black, N,N-dimethylformamide, intermediate 3, and DCC is 1g:100mL:8.3g:3.5g;

[0022] The surface of oxidized carbon black contains a large number of oxygen functional groups, which can react with the amino groups in the intermediate 3 molecules under the catalysis of DCC, and graft organic molecules on the surface of oxidized carbon black to obtain modified carbon black;

[0023] Carbon black has excellent electrical conductivity and certain flame retardant properties. The surface of carbon black is modified by using organic molecular chains. The ester group, amide group, benzene ring and long carbon chain in the organic molecular chain are all hydrophobic, which can enhance the surface hydrophobicity of carbon black, thereby improving the interfacial compatibility between carbon black and polyurethane matrix. It not only promotes the dispersion of carbon black and reduces its influence on the mechanical properties of the matrix, but also makes the performance of carbon black fully exerted, greatly enhancing the shielding performance and certain flame retardant properties of the matrix. In addition, the modified carbon black contains diphenyl sulfone, hindered amine and long carbon chain structure, among which diphenyl sulfone can not only enhance the matrix The heat resistance of the matrix is ​​improved, and the S element in the diphenyl sulfone structure generates SO2, sulfurous acid and water during thermal desulfurization, which can promote the Fries rearrangement reaction of the matrix and accelerate the carbonization of the matrix. It can work synergistically with carbon black to significantly enhance the flame retardant and smoke suppression properties of the matrix. The introduced hindered amine will decompose hydrogen dioxide to produce stable nitroxide free radicals. This compound can very effectively capture the free radicals generated during oxidative degradation and improve the aging resistance of the matrix. Finally, the introduced long carbon chain belongs to a flexible chain segment, which can not only improve the flexibility of the matrix, but also be interspersed in the macromolecular chain of the matrix to improve stability.

[0024] It should be further explained that the grafting of organic molecular chains on the surface of carbon black can effectively inhibit the migration and infiltration of small organic molecules, making the performance of modified carbon black more stable.

[0025] Further, the oxidized carbon black is prepared by the following steps:

[0026] Add carbon black to a three-necked flask equipped with a stirring device, and then drop nitric acid solution (mass fraction 68%) into the device. After the dropwise addition is completed, heat to 50°C, stir and react for 2 hours. After the reaction is completed, filter, wash with water 3-4 times, and dry to obtain oxidized carbon black; the ratio of carbon black to nitric acid solution is 1g:20mL.

[0027] Beneficial effects of the present invention:

[0028] 1. The composite material prepared by the present invention uses polyurethane as a matrix, which gives the material excellent flexibility;

[0029] 2. The introduction of polypyrrole enhances the electromagnetic shielding property of the composite material;

[0030] 3. By modifying the surface of carbon black, compared with ordinary carbon black, it has better compatibility with the polyurethane matrix, significantly reduces the agglomeration phenomenon, and is easier to disperse in the matrix, which greatly enhances the flame retardancy, shielding and flexibility of the composite material. The performance is long-lasting and stable, and it is not easy to fall off;

[0031] Therefore, the composite material prepared by the present invention has stable and efficient electromagnetic shielding, flexibility and flame retardancy, and has important application value in the field of electromagnetic shielding technology. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Embodiment 1

[0034] Preparation of oxidized carbon black:

[0035] Add 1 g of carbon black to a three-necked flask equipped with a stirring device, and then add 20 mL of nitric acid solution (mass fraction 68%) dropwise into the device. After the addition is completed, heat to 50°C, stir and react for 2 hours. After the reaction is completed, filter, wash with water 3 times, and dry to obtain oxidized carbon black.

[0036] Embodiment 2

[0037] Preparation of modified carbon black:

[0038] S1. In a three-necked flask equipped with a stirring reflux device, 15.7 g of 2,2,6,6-tetramethylpiperidinol, 75 mL of n-octane, and 0.2 g of molybdenum trioxide were mixed and stirred evenly, and 15 mL of tert-butyl hydroperoxide aqueous solution (mass fraction 8%) was added dropwise, and stirring was performed while adding dropwise until the addition was completed. The reaction temperature was controlled to 75° C., and the reflux reaction was performed for 6 h. After the reaction was completed, the mixture was filtered, and activated carbon was added to the filtrate and stirred for 1 h. The mixture was allowed to stand, filtered, and the filtrate was taken. The n-octane was removed by distillation under reduced pressure to obtain intermediate 1.

[0039] S2, in a three-necked flask equipped with a stirring device, 18.1g of terephthalic acid, 28.5g of intermediate 1 and 150mL of N,N-dimethylformamide were stirred and mixed uniformly, 0.2g of 4-dimethylaminopyridine and 20.6g of dicyclohexylcarbodiimide were added, the reaction temperature was controlled to 75°C, and the reaction was kept warm for 8h, with continuous stirring during the reaction. After the reaction was completed, the reaction was filtered, and part of the solvent was removed by distillation under reduced pressure, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 4:1), and the eluent was removed by rotary evaporation to obtain intermediate 2;

[0040] S3, add 25.7g 4,4'-diaminodiphenyl sulfone and 150mL N,N-dimethylformamide to a three-necked flask equipped with a stirring device, heat to 30°C and stir continuously until the solid is completely dissolved, introduce nitrogen to exclude air, add 43.3g intermediate 2 and 20.6g DCC, mix and stir evenly, place in a 55°C water bath, stir and react for 4h, filter after the reaction, remove the solvent by distillation under reduced pressure, wash twice with anhydrous ethanol, and vacuum dry to obtain intermediate 3;

[0041] S4. In a three-necked flask equipped with a stirring device, mix 1 g of oxidized carbon black with 100 mL of N,N-dimethylformamide, and perform ultrasonic treatment for 15 min to evenly disperse the oxidized carbon black. Add 8.3 g of intermediate 3 and 3.5 g of DCC, and perform magnetic stirring for 2 h. Then, place in a 55°C water bath and perform ultrasonic treatment for 4 h. Remove the water bath and perform magnetic stirring for 6 h at room temperature. Filter, wash with anhydrous ethanol 4 times, dry, and grind to obtain modified carbon black.

[0042] Embodiment 3

[0043] Preparation of modified carbon black:

[0044] S1. In a three-necked flask equipped with a stirring reflux device, 31.4 g of 2,2,6,6-tetramethylpiperidinol, 150 mL of n-octane, and 0.4 g of molybdenum trioxide were mixed and stirred evenly, and 30 mL of tert-butyl hydroperoxide aqueous solution (mass fraction 8%) was added dropwise, and stirring was performed while adding dropwise until the addition was completed. The reaction temperature was controlled to 75° C., and the reflux reaction was performed for 6 h. After the reaction was completed, the mixture was filtered, and activated carbon was added to the filtrate and stirred for 1 h. The mixture was allowed to stand, filtered, and the filtrate was taken. The n-octane was removed by vacuum distillation to obtain intermediate 1.

[0045] S2, in a three-necked flask equipped with a stirring device, 36.2g of terephthalic acid, 57g of intermediate 1 and 300mL of N,N-dimethylformamide were stirred and mixed uniformly, 0.4g of 4-dimethylaminopyridine and 41.2g of dicyclohexylcarbodiimide were added, the reaction temperature was controlled to 75°C, and the reaction was kept warm for 8h, and stirring was continued during the reaction. After the reaction was completed, the reaction was filtered, and part of the solvent was removed by vacuum distillation, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 4:1), and the eluent was removed by rotary evaporation to obtain intermediate 2;

[0046] S3, add 51.4g 4,4'-diaminodiphenyl sulfone and 300mL N,N-dimethylformamide to a three-necked flask equipped with a stirring device, heat to 30°C and stir continuously until the solid is completely dissolved, introduce nitrogen to exclude air, add 86.6g intermediate 2 and 41.2g DCC, mix and stir evenly, place in a 55°C water bath, stir and react for 4h, filter after the reaction, remove the solvent by distillation under reduced pressure, wash twice with anhydrous ethanol, and vacuum dry to obtain intermediate 3;

[0047] S4. In a three-necked flask equipped with a stirring device, mix 2 g of oxidized carbon black with 200 mL of N,N-dimethylformamide, and perform ultrasonic treatment for 15 min to evenly disperse the oxidized carbon black. Add 16.6 g of intermediate 3 and 7 g of DCC, and perform magnetic stirring for 2 h. Then, place in a 55°C water bath and perform ultrasonic stirring for 4 h. Remove the water bath and perform magnetic stirring for 6 h at room temperature. Filter, wash with anhydrous ethanol 4 times, dry, and grind to obtain modified carbon black.

[0048] Embodiment 4

[0049] 60g of polyurethane and 25g of polypyrrole were dried, added into a mixer with 12g of the modified carbon black prepared in Example 1 and 4g of stearic acid, stirred evenly, and then put into a twin-screw extruder, set the temperature to 200°C, melt blended for 30min, and extruded to obtain a flexible shielding composite material.

[0050] Embodiment 5

[0051] 70g of polyurethane and 30g of polypyrrole were dried, added into a mixer with 20g of the modified carbon black prepared in Example 1 and 5g of paraffin wax, stirred evenly, and then put into a twin-screw extruder, set the temperature to 210°C, melt blended for 45min, and extruded to obtain a flexible shielding composite material.

[0052] Embodiment 6

[0053] 80g of polyurethane and 35g of polypyrrole were dried, added into a mixer with 28g of modified carbon black prepared in Example 2 and 6g of paraffin wax, stirred evenly, and then put into a twin-screw extruder, set the temperature to 220°C, melt blended for 60min, and extruded to obtain a flexible shielding composite material.

[0054] Comparative Example 1

[0055] The modified carbon black in Example 5 was replaced by commercially available ordinary carbon black of equal quality, and the remaining steps were the same as those in Example 5 to obtain the material.

[0056] Comparative Example 2

[0057] Use commercially available flexible electromagnetic shielding materials.

[0058] Embodiments 4, 5, 6, and comparative examples 1 and 2 were made into corresponding shapes according to different test standards, and the following performance tests were performed:

[0059] The tensile strength is determined using the national standard GB / T 1040.2-2022 "Determination of tensile properties of plastics";

[0060] The notched impact strength is tested according to the national standard GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics";

[0061] The sample was placed in a xenon lamp aging test chamber for accelerated aging for 30 days. The aging conditions were air atmosphere, xenon lamp wavelength 280-800nm, and irradiation intensity 550W / m 2, test the notched impact strength of the sample after aging (GB / T 1043.1-2008), and calculate the notched impact strength retention rate; notched impact strength retention rate = notched impact strength after test / notched impact strength before test × 100%;

[0062] The electromagnetic shielding performance was tested using a shielding effectiveness tester, with the frequency band set at 8.2-12.4GHz;

[0063] The oxygen index was determined using the national standard GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method", and then Examples 3, 4, and 5 were placed at room temperature for 100 days, and the oxygen index after 100 days was determined;

[0064] The measured results are shown in the following table:

[0065]

[0066] It can be seen from the above table that the flexible shielding composite material prepared in the embodiment of the present invention has excellent electromagnetic shielding properties, and its flexibility and flame retardancy are higher than those of the control example, and its flame retardancy is long-lasting and stable. Therefore, the present invention has important application value in the field of electromagnetic shielding technology.

[0067] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0068] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a flexible shielding composite material, characterized in that: The following steps are involved: The polyurethane and polypyrrole are dried, added into a mixer with modified carbon black and a lubricant, stirred evenly, and then put into a twin-screw extruder for melt blending and extrusion to obtain a flexible shielding composite material.

2. The method for preparing a flexible shielding composite material according to claim 1, characterized in that: The modified carbon black is prepared by the following steps: S1. Mix 2,2,6,6-tetramethylpiperidinol, n-octane and molybdenum trioxide and stir evenly, add tert-butyl hydroperoxide aqueous solution dropwise, stir while adding until the addition is complete, reflux at 75°C for 6h, filter after the reaction is complete, add activated carbon to the filtrate and stir for 1h, let stand, filter, take the filtrate, and distill under reduced pressure to obtain intermediate 1; S2, terephthalic acid, intermediate 1 and N,N-dimethylformamide were stirred and mixed evenly, 4-dimethylaminopyridine and dicyclohexylcarbodiimide were added, and the mixture was kept warm at 75°C for 8 hours with continuous stirring during the reaction. After the reaction was completed, the mixture was filtered, distilled under reduced pressure, purified by column chromatography, and rotary evaporated to obtain intermediate 2; S3, 4,4'-diaminodiphenyl sulfone and N,N-dimethylformamide were mixed, heated to 30°C and stirred continuously until the solid was completely dissolved, nitrogen was introduced to exclude air, intermediate 2 and DCC were added and mixed and stirred evenly, placed in a 55°C water bath, stirred and reacted for 4 hours, and after the reaction was completed, filtered, vacuum distilled, washed, and vacuum dried to obtain intermediate 3; S4. Mix the oxidized carbon black with N,N-dimethylformamide, perform ultrasonic treatment for 15 minutes to evenly disperse the oxidized carbon black, add intermediate 3 and DCC, perform magnetic stirring for 2 hours, place in a 55°C water bath for ultrasonic treatment for 4 hours, perform magnetic stirring at room temperature for 6 hours, filter, wash, dry and grind to obtain modified carbon black.

3. The method for preparing a flexible shielding composite material according to claim 2, characterized in that: In step S1, the ratio of the amount of 2,2,6,6-tetramethylpiperidinol, n-octane, molybdenum trioxide, and tert-butyl hydroperoxide aqueous solution is 15.7 g:75 mL:0.2 g:15 mL.

4. The method for preparing a flexible shielding composite material according to claim 2, characterized in that: In step S2, the ratio of the amount of terephthalic acid, intermediate 1, N,N-dimethylformamide, 4-dimethylaminopyridine and DCC is 18.1 g: 28.5 g: 150 mL: 0.2 g: 20.6 g.

5. The method for preparing a flexible shielding composite material according to claim 2, characterized in that: In step S3, the ratio of 4,4'-diaminodiphenyl sulfone, N,N-dimethylformamide, intermediate 2, and DCC is 25.7 g: 150 mL: 43.3 g: 20.6 g.

6. The method for preparing a flexible shielding composite material according to claim 2, characterized in that: In step S4, the ratio of oxidized carbon black, N,N-dimethylformamide, intermediate 3, and DCC is 1 g:100 mL:8.3 g:3.5 g.

7. The method for preparing a flexible shielding composite material according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 60-80 parts of polyurethane, 25-35 parts of polypyrrole, 12-28 parts of modified carbon black, and 4-6 parts of lubricant.

8. A flexible shielding composite material, characterized in that: Prepared according to the method according to any one of claims 1 to 7.